Resistividade, potencial espontâneo e radiometria aplicados a investigações ambiental e forense no campo de testes do cemitério do Tapanã (Belém-PA) - COSTA, Anderson Antonio Santiago da (2019)
In continuity to the studies of the UFPA in cemeteries, a site for controlled tests was implanted in the cemetery of the Tapanã in 2007. Three targets were buried under a profile: a human body, a tunnel and a box with material simulating military weapons. The objective was to investigate the answers of the geophysical methods electrorresistivity, spontaneous potential and radiometry to the body decomposition throughout the time in order to subsidize ambient inquiries on the signature of the plume of contamination of the necroleachate. Moreover, being the three also material targets of police inquiries, we searched the applicability of those methods in forensic geophysics. The results gotten with electrorresistivity allowed to identify the ground dug. The results with spontaneous potential showed an increase in voltage on the corpse. Radiometry showed that the corpse and the tunnel increased the background. The results shown here evidence that the used methods have potential for environmental studies in cemeteries and forensic investigation in the following order: electrorresistivity, spontaneous potential and radiometry.